Selective Growth of Metal Sulfide, Metal, and Metal-Alloy on 2D CdS Nanoplates - Fridman, Helena; Tian, Liang; Shreteh, Karam; Volokh, Michael; Mokari, Taleb (Frontiers in Materials, 2020)
Two-dimensional CdS-based hybrid nanostructures are intriguing materials with an application prospect in different fields such as sensing (i.e., photoresistors) and solar energy harvesting (photocatalysis, photovoltaics, and so forth). We report herein a colloidal synthetic path for interfacing metal and semiconductor with 2D CdS nanoplates. Selective growth of Au, Pt, and a PtNi alloy as well as Cu2–xS semiconductor is achieved on CdS nanoplates using controlled reduction of metallic precursors and thermal decomposition of a metal-sulfide single-source precursor using standard organic-phase colloidal chemistry.